Effect of magnesium foliar application at different phenological stages in soybean and maize plants - Tacca, Julio Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Magnesium is an overlooked nutrient due to the paucity of research on it. In addition, it is found in low amounts in the soil, possibly due to anthropogenic activities, such as excessive potassium fertilization. The consequence of this is an antagonism of magnesium absorption, resulting in limited productivity. Since nitrogen fertilization in the soybean crop is unnecessary due to symbiosis with bacteria of the genus Rhizobium, magnesium plays a fundamental role in biological nitrogen fixation. In addition, it activates more than 300 enzymes and when it is deficient in plants, it causes a reduction in productivity. This study will provide relevant information regarding the role of magnesium in photosynthesis, biological nitrogen fixation and protein synthesis.

O magnésio é um nutriente negligenciado devido à escassez de pesquisas sobre ele. Além disso, é encontrado em baixa quantidade no solo, possivelmente devido a atividades antrópicas, como fertilização excessiva com potássio. A consequência disso é um antagonismo de absorção de magnésio, resultando em produtividade limitada. Como a adubação nitrogenada em a cultura da soja é desnecessária devido à simbiose com bactérias do gênero Rhizobium, magnésio desempenha um papel fundamental na fixação biológica de nitrogênio. Em Além disso, ativa mais de 300 enzimas e, quando deficiente nas plantas, causa uma redução na produtividade. Este estudo fornecerá informações relevantes sobre a papel do magnésio na fotossíntese, fixação biológica de nitrogênio e síntese de proteínas.
Efeito da aplicação foliar de magnésio em diferentes estádios fenológicos de soja e milho
Keywords: Photosynthesis; Antagonism; Magnesium; Potassium